Performance Audit on Functioning of Select Govt Medical Colleges and Teaching Hospitals in Gujarat (2012-2017) - CAG of India (CAG of India, 2020)
The mission of the Health and Family Welfare Department of Government of Gujarat is to increase life expectancy through various health and medical interventions contributing to overall improvement in Human Development Index of Gujarat to a level comparable with developed countries. The vision of the department is to improve physical quality of life of people of Gujarat so that they attain the highest level of physical, mental and spiritual health and contribute towards the development of the State. The main objectives of the department are reducing maternal and child mortality, and creating adequate infrastructure and educational facilities for medical and para-medical education to produce medical manpower to provide quality healthcare services. For providing equitable access to affordable, accountable and quality healthcare to the citizens, adequate healthcare infrastructure with trained medical human resource is a pre-requisite. Medical education is meant to make available services of doctors in Government as well as private hospitals of the State to cater to the health needs. As of March, 2017, there are six Government Medical Colleges (GMCs) with an annual intake capacity of 1,080 and 750 for Under Graduate (UG) and Post Graduate (PG) courses respectively. “Working of select Government Medical Colleges and attached Teaching Hospitals (THs)” was taken up in audit between March and August 2017, for their performanfcroem the year 2012 to 2017. Audit revealed that important areas of medical education and delivery of quality healthcare services in the attached teaching hospitals required immediate attention of Government and prompt remedial action for augmentation of medical education and quality healthcare. A few instances have been highlighted below — 1. State Government could not avail of central funds of INR 750 crore for establishment of five new medical colleges in the State under Centrally Sponsored Scheme due to delay in submission of proposals by the State Government. 2. Targets set (2012-15) for increasing the intake capacity of UG, PG and Super-Specialty courses has been partially achieved as of March 2017. 3. In test-checked GMCs, prescribed infrastructure and other facilities for proper teaching was found deficient. Lecture theatres were not equipped for virtual class lecture. Due to inadequate capacity in the hostels, students were found accommodated on floor beds and four to five students in a room. 4. Central Casualty Department of Civil Hospitals (CHs), Jamnagar and Surat were functioning without Intensive Care Units (ICUs) and had lesser number of beds than prescribed by the Medical Council of India (MCI). Number of beds in ICUs of test-checked CHs was less than those prescribed by Indian Public Health Standards. The ICUs were not fully equipped to handle critical cases. The bed capacity of test-checked CHs attached with GMCs remained unchanged despite increase in number of indoor patients during 2012-17. 5. Objectives of Pradhan Mantri Swasthya Surakhsha Yojana (PMSSY) to augment medical education and to strengthen the healthcare facilities were only partially achieved due to non-procurement of equipment by B. J. Medical College (BJMC), Ahmedabad under the project. 6. Norms prescribed by MCI for teaching, clinical postings and exposure of students to clinical units and training centres were not adhered to by the test-checked GMCs. 7. Medical Education and healthcare suffered due to shortage in the cadre of teaching staff. Instances of en-masse transfer of teachers from one Medical College (MC) to the other MCs, prior to inspection of MCI for retaining the licence of the college were noticed in Audit. 8. State Government had not framed any guidelines for promotion of research in Medical Colleges. Research aspirants in the State have not received any financial assistance for research activities since 2014-15. 9. Monitoring of education imparted in GMCs was found deficient.